2023
DOI: 10.1161/atv.0000000000000164
|View full text |Cite|
|
Sign up to set email alerts
|

Aggressive LDL-C Lowering and the Brain: Impact on Risk for Dementia and Hemorrhagic Stroke: A Scientific Statement From the American Heart Association

Larry B. Goldstein,
Peter P. Toth,
Jennifer L. Dearborn-Tomazos
et al.

Abstract: The objective of this scientific statement is to evaluate contemporary evidence that either supports or refutes the conclusion that aggressive low-density lipoprotein cholesterol lowering or lipid lowering exerts toxic effects on the brain, leading to cognitive impairment or dementia or hemorrhagic stroke. The writing group used literature reviews, references to published clinical and epidemiology studies, clinical and public health guidelines, authoritative statements, and expert opinion to summarize existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 225 publications
0
4
0
Order By: Relevance
“…A recent study [24] found that higher LDL-C levels were associated with a lower risk of major depressive disorder (MDD), whereas one relatively recent case-control study found that higher LDL-C and total cholesterol levels and lower HDL-C levels were connected to anxiety disorder risk [25]. There are numerous gaps in our understanding of the role of cholesterol and its biosynthesis, so at this moment we could only suggest reasons for the described connection between "spontaneous" low LDL and psychological disorders in ACS patients [26]. Whatever the reason for that finding, it is clear from our data and from previous research [27], that psychological disorders are linked with worse outcomes after ACS.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study [24] found that higher LDL-C levels were associated with a lower risk of major depressive disorder (MDD), whereas one relatively recent case-control study found that higher LDL-C and total cholesterol levels and lower HDL-C levels were connected to anxiety disorder risk [25]. There are numerous gaps in our understanding of the role of cholesterol and its biosynthesis, so at this moment we could only suggest reasons for the described connection between "spontaneous" low LDL and psychological disorders in ACS patients [26]. Whatever the reason for that finding, it is clear from our data and from previous research [27], that psychological disorders are linked with worse outcomes after ACS.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, aggressive lowering of LDL cholesterol by statins was inconsistently associated with ICH and dementia in observational studies, 120,121 which could be relevant in patients with cSVD. Conversely, more recent evidence failed to find such associations.…”
Section: Hyperlipidemia and Statinsmentioning
confidence: 99%
“…Overall available evidence suggests that the protection against atherosclerotic cardiovascular disease with lowering LDL cholesterol outweighs the potential risk of ICH among patients with high atherosclerotic cardiovascular disease risks. 121…”
Section: Hyperlipidemia and Statinsmentioning
confidence: 99%
“…Although the IMPROVE-IT trial found a non-significant trend towards increased hemorrhagic stroke in those treated to a lower LDL-C goal with ezetimibe and simvastatin, a subsequent 2017 analysis showed significant reductions in major adverse cardiovascular events (MACE) with LDL-C < 30 mg/dL compared to ≥70 mg/dL, without a concomitant increase in rates of neurocognitive events, hemorrhagic stroke, or non-CVD deaths [58,99]. The American Heart Association recently published a scientific statement on LDL-C lowering and the risk for dementia and hemorrhagic stroke, stating that achieving very low LDL-C does not increase the risk for hemorrhagic stroke and that the risk of a hemorrhagic stroke associated with statin therapy in patients without a history of cerebrovascular disease is small and consistently nonsignificant [100].…”
Section: Benefits and Risks Of Very Low Ldl-cholesterolmentioning
confidence: 99%